Operational validity of the Es:Ep ratio for source mechanism classification in a block cave with a dense seismic network - Morkel, IG (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
The ratio of S-wave to P-wave energy (Es/Ep) is a traditional parameter in mine seismology, used empirically to distinguish between shear and non-shear failure mechanisms. While moment tensor inversion (MTI) provides a far more complete physical representation of seismic sources, the Es/Ep parameter remains a practical tool for rapid assessment and back-analysis of historical catalogues. However, the reliability of standard Es/Ep thresholds is increasingly questioned due to inherent data quality challenges. This paper evaluates the operational validity of the Es/Ep parameter by statistically comparing it against the automated MTI results from a densely seismically instrumented block cave mine. The Matthews correlation coefficient is used to assess classification confidence. Across the full catalogue, the standard thresholds gave a poor correlation, driven by a dominance of MTI shear events at low Es/Ep values. The MTI reference is itself automated and coverage-dependent, so the comparison measures agreement between 2 imperfect estimators, and the conclusions are conditional on the MTI being the more reliable of the 2. Progressive filtering by the number of sensors used showed that strict sensor requirements raise the correlation to a reliable level, but at the cost of discarding the large majority of the dataset. Site-specific calibration restores diagnostic confidence yet leaves only a small fraction of events usable for single event analysis.
Keywords: mine seismology; Es/Ep; Es:Ep ratio; seismic mechanisms; moment tensor inversion